Implementation of Character Education through Distance Learning during Covid-19 Pandemic (Journal of Primary Education, 2022)
The Covid-19 emergency has caused a shift in learning. Learning activities that were previously carried out in classroom now have to be done at home or study from home. The Covid-19 Emergency Period makes students often interact with gadgets. It is predicted in the future that Gen A students have less socialization problems, less creativity and more individualistic attitude. Continuous use of gadgets also has the potential to make them socially isolated. Character education must continue during the distance learning period. The purpose of this study was to analyze the character values that can be developed in Distance Learning (PJJ) at State Islamic Elementary School Four of Boyolali Regency by implementing learning media. The research method used is field research with a qualitative approach through field observations, interviews and documentation. Data collection techniques are using observation methods, interview methods and documentation. The principals, teachers, parents, and students were involved in this research. Data data reduction, data display, conclusion drawing/verification were employed to gain the goals. The results of the research on the implementation of character education in the online learning by integrating them in the thematic learning. Planning, implementation, and evaluation approach were conducted by the teachers in distance learning model. Character values that can be developed in distance learning are religious values, nationalist values, independent values, mutual cooperation values and integrity values. Based on the results of the study, it can be concluded that online learning media plays an important role in developing character education through learning activities by utilizing learning media during the Covid-19 pandemic.